PENGARUH PROFITABILITAS, SOLVABILITAS, PERGANTIAN AUDITOR TERHADAP AUDIT DELAY DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Erlisa Santri; Novita Indrawati; Fitri Humairoh (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study aims to examine the influence of profitability, solvency, and auditorchange on audit delay, with company size as a moderating variable. The dataused in this study are secondary data. The sampling technique used was purposivesampling, resulting in 101 companies with a four-year observation period,resulting in a total sample of 156. Data analysis techniques used were multiplelinear regression analysis and moderated regression analysis (MRA) using SPSS26 software. The results concluded that profitability, solvency, and auditor changehad no effect on audit delay. Company size did not moderate the effect ofprofitability, solvency, and auditor change on audit delay.Keywords: Profitability, Solvency, Auditor Change, Company Size, and AuditDelay